Structure, optical and electrical properties of polyaniline encapsulated nickel, cobalt, and chromium nanoparticles synthesized by gamma radiation - Ali Meftah, Abdo Mohammed (2012)
Nanomaterials have attracted much attention recently because of their many applications including in catalysis, microelectronics, biomedicine and photovoltaics. The composites of conducting polymer – magnetic metal nanoparticles are promising candidates based on the fact that the small sized particles enhance their physical properties while the conducting polymer matrix present electrical host – guest interaction to have a new magneto-electric phenomenon to occur at the same time, allowing coupling between magnetic and electric properties for future devices. Among the conducting polymers, polyaniline (PANI) has been of particular interest because of its environmental stability and controllable electrical conductivity and dissipation of electrostatic charges. In this work PANI was used to encapsulate nickel (Ni), cobalt (Co), and chromium (Cr) magnetic nanoparticles in polyvinyl alcohol.\ (PVA) aqueous and film matrix. The solution composites were synthesized from aniline monomer (0.067 g), nickel, cobalt, and chromium chlorides at different concentrations (0.017, 0.025, 0.033, 0.042, and 0.5 g), and PVA (0.1 g), 10 ml deionized water and completed by irradiation at doses of 0, 1, 2, 3, 4, 5 and 6 kGy. The film composites were made from aniline monomer (4 g), nickel, cobalt, and chromium chlorides at different concentrations (1, 1.5, 2, 2.5, and 3 g), and PVA (6 g) and completed by gamma irradiation at doses of 0, 10, 20, 30, 40 and 50 kGy. No chemical reducing or oxidising agent was used to synthesis metal nanoparticles or PANI. The structural and morphology of metal nanoparticles in PVA solutions were studied using x-ray diffraction, atomic force microscopy, photon cross correlation spectroscopy, and transmission electron microscopy. The average particle size distributions in solution were found in the range of 22 – 54 nm for Ni nanoparticles, 14 – 50 nm for Co nanoparticles and 3 – 13 nm for Cr nanoparticles. The particle sizes of metal nanoparticles were controlled by the concentration of metal ions and radiation doses. The average diameter of Ni, Co and Cr nanoparticles decreased exponentially with the increase of dose D and fitted the expression of d = dmax – B(1-e-D/D 0), with D0 equal 2.2, 1.53, and 1.4 kGy for Ni, Co and Cr nanoparticles respectively. A UV-visible spectrophotometer was used to measure optical characteristics of composites of PANI/Ni, PANI/Co and PANI/Cr nanoparticles. The maximum absorbance peaks max appear at about 395, 520, 420 nm for Ni, Co, Cr nanoparticles respectively for both solution and film composites. The absorption peaks λmax blueshift towards shorter wavelengths with the increase of dose attributing to a decrease in the average diameter of metal nanoparticles with increasing dose. As a result, the conduction band increases with increase of radiation dose or decrease of particle size. The confinement effects of conducting band can be explained fundamentally in terms of the quantum mechanical description in which by reducing the nanoparticle size, the number of atoms to form a nanoparticle is also reduced and less protons attracting the conduction electrons, thus enlarging the conduction band energy of metal nanoparticles. The optical absorbance peaks of PANI in solution composites appear at 620, 670, and 580 nm for PANI/Ni, PANI/Co, and PANI/Cr nanoparticles respectively. However, the absorbance peaks shifted to 720, 670, and 580 nm for film composites of PANI/Ni, PANI/Co and PANI/Cr nanoparticles respectively. The band gap of PANI decreased with increase of dose and increased with increase of chloride ion concentration. When the dose increased from 10 to 50 kGy, the band gap of PANI films decreases from 1.56 to 1.4 eV and from 1.54 to 1.33 eV for 10, and 22.5 wt% NiCl2 respectively; from 1.8 to 1.71 eV and from 1.72 to 1.67 eV for 10 and 22.5 wt% CoCl2 respectively; and from 1.92 to 1.87 eV and from 1.89 to 1.83 eV for 10 and 22.5 wt% CrCl3 respectively. The conductivity measurement reveals that the dc conductivity of PANI in film composites increased with increase of dose and ion concentration. When the dose increased from 10 to 50 kGy, the conductivity of PANI decreases from 2.38 × 10-4 to 5.98 × 10-3 (S/m) and from 7.10 × 10-4 to 3.48 × 10-2 (S/m) for 10 and 22.5 wt% of NiCl2 respectively; from 1.13 × 10-4 to 2.01 × 10-3 (S/m) and from 7.16 × 10-4 to .03 × 10-2 (S/m) for 10 and 22.5 wt% of CoCl2 respectively; from 3.68 × 10-5 to 1.60 × 10-3 (S/m) and from 2.69 × 10-4 to 1.68 × 10-3 (S/m) for 10 and 22.5 wt% of CrCl3 respectively. The dc conductivity has an exponential expression of the form: dc = 0 exp (D/D0), where the 0 and D0 vary with ion concentration.